Feasibility Evaluation Of Passenger Piers At Jangari Pier, Cirata Reservation, West Java Province - Irwan Irwan; Broto Priyono; Daffa Hanifah (IWJ : Inland Waterways Journal, 2022)
Jangari Pier is the most active activity point in the Cirata Reservoir, West Java Province, located in Cianjur Regency. The water activities in the Cirata Reservoir consist of the tourism, fisheries, and water transportation activities carried out under the supervision of the Transportation Agency in the Cirata Reservoir Environment on the basis of a cooperation agreement between the reservoir manager, namely PT PJB UP Cirata and UPTD PPP LLASDP West Java Province which placing the Cirata LLASD Service Unit, with an operating license agreement in the form of supervision of water transportation activities in the Cirata Reservoir. Water transportation is one of the most important and strategic aspects in facilitating the wheels of development, and strengthening unity and integrity, in the water transportation sector which requires comfortable and proper passenger transportation facilities in accordance with guidelines and standards. Guidelines regarding standard facilities and dock dimensions that are suitable for ships operating in passenger boarding activities at Jangari Pier based on dock analysis in the dock planning book by Bambang Triatmodjo in 2010 and Director General of Land Transportation Regulation number: KP.4756/AP005/DRJD/2020 regarding the Technical Guidelines for the Sungai Danau Stop by evaluating passenger boarding and descending activities to determine the type of pier that is in accordance with the characteristics of the Cirata reservoir so that passenger boarding and descending activities are safe, and comfortable in accordance with the calculations carried out with the aim that passenger boarding activities take place optimally.